Methyl-CpG-binding domain sequencing reveals a prognostic methylation signature in neuroblastoma - Decock, Anneleen; Ongenaert, Maté; Cannoodt, Robrecht; Verniers, Kimberly; De Wilde, Bram; Laureys, Geneviève; Van Roy, Nadine; Berbegall, Ana P; Bienertova-Vasku, Julie; Bown, Nick; Clément, Nathalie; Combaret, Valérie; et al. (Oncotarget, 2016)
Accurate assessment of neuroblastoma outcome prediction remains challenging. Therefore, this study aims at establishing novel prognostic tumor DNA methylation biomarkers. In total, 396 low- and high-risk primary tumors were analyzed, of which 87 were profiled using methyl-CpG-binding domain (MBD) sequencing for differential methylation analysis between prognostic patient groups. Subsequently, methylation-specific PCR (MSP) assays were developed for 78 top-ranking differentially methylated regions and tested on two independent cohorts of 132 and 177 samples, respectively. Further, a new statistical framework was used to identify a robust set of MSP assays of which the methylation score (i.e. the percentage of methylated assays) allows accurate outcome prediction. Survival analyses were performed on the individual target level, as well as on the combined multimarker signature. As a result of the differential DNA methylation assessment by MBD sequencing, 58 of the 78 MSP assays were designed in regions previously unexplored in neuroblastoma, and 36 are located in non-promoter or non-coding regions. In total, 5 individual MSP assays (located in CCDC177, NXPH1, lnc-MRPL3-2, lnc-TREX1-1 and one on a region from chromosome 8 with no further annotation) predict event-free survival and 4 additional assays (located in SPRED3, TNFAIP2, NPM2 and CYYR1) also predict overall survival. Furthermore, a robust 58-marker methylation signature predicting overall and event-free survival was established. In conclusion, this study encompasses the largest DNA methylation biomarker study in neuroblastoma so far. We identified and independently validated several novel prognostic biomarkers, as well as a prognostic 58-marker methylation signature.
Keywords: DNA, Neoplasm; Real-Time Polymerase Chain Reaction; prognosis; kojenec; výpočetní biologie; Prognosis; Cohort Studies; CpG Islands; mužské pohlaví; Infant; Tumor Cells, Cultured; CpG ostrůvky; Neuroblastoma; kohortové studie; kvantitativní polymerázová řetězová reakce; DNA methylation; Neoplasm Staging; biomarker; neuroblastoma; ženské pohlaví; prognóza; Humans; metylace DNA; Binding Sites; biologické markery; DNA nádorová; DNA Methylation; staging nádorů; Biomarkers; Computational Biology; neuroblastom; Female; nádorové buňky kultivované; vazebná místa; lidé; Male